Pengaruh Stock Split Terhadap Likuiditas Saham DanAbnormal Return Saham Pada Perusahaan YangTerdaftar Di Bei Tahun 2010-2014 - Putri, Dewi Septiana; , Imron Rosyadi, SE., M.Si (2017)
Stock split is action by companies with the goal set back the stock price to be a more liquid and provide more positive signal to investor. The purpose of this research is to analyze the differences in the liquidity of the stock and the abnormal return before and after the announcement of a stock split, so that investors could use this stock split event to gain benefit. This research uses event study method, to observed average trading volume activity and abnormal return for five days before and five days after event date. This research uses secondary data obtained from the Indonesian Capital Market Directory (ICMD) 2010 up to 2014, www.idx.co.id, and http://finance.yahoo.com/. The data used in this research include the date of the announcement of stock split which is used as the event date (t), closing stock price of the companies applying stock split in the observation period, Composite Stock Price Index (IHSG), the amount of daily traded share and the amount of listed share. There are 23 companies for this research, they are stock split of the companies which implemented stock split within 2010 up to 2014 and listed in BEI. The results from this research is there are no significant difference of stock liquidity and abnormal return before and after event of stock split. Suggestions relating to the results of this research is: not all of the capital market information is good information, for that investors should be able to sort out the information as a consideration of investment decision.